Development and scaling of mobile seed cleaning technology to improve forage seed quality and generate income for farmer groups in Tunisia - CGIAR Research Program on Livestock (2021)
Many CGIAR centers are developing forage crops, but seed quality declines once farmers reproduce the seeds for planting. With this simple mobile seed cleaning and treatment unit, seed quality and production capacity can be maintained sustainably. Four farmer cooperatives in North-western Tunisia with over 1,000 members are using the technology, and from October 2019-December 2021 the quantity of cleaned/treated forage seeds increased from 240 to 908 tons and the number of individual users from 138 to 417.